Juventude rural e produção de cannabis na fronteira seca Brasil - Paraguai - Mendoza, Benito Armando Solis (2013)
The thesis studies linking rural youth in the production of Cannabis sativa in the region of dry border of Paraguay and Brazil. In the 1980s, criminal organizations started to explore the production of the drug, taking advantage of the advantages agro-climatic regional actions and the lack of effective control. The region has become a major producer of drugs and began to incorporate rural youth in illicit activities. The objective of the research is to understand the reasons why rural youth link up the activities of production, processing and transportation of cannabis, highlighting the conditions and risks of illicit work. The research follows a qualitative approach and the survey was conducted at the Department of Amambay in the municipalities of Pedro Juan Caballero and Capitán Bado. The main technique of data collection was semi-structured interviews, conducted for ten young rural sixteen key informants and two-parent families. The interviews were complemented with free observation, the literature search and survey documents. Linking young people in the production of cannabis is associated with lack of profitable alternative licit agricultural production and qualification of young people working for other occupations that offer opportunities to build personal autonomy and a promising future. The lack of public policies for rural youth is exploited by criminal organizations to incorporate youth in impoverished rural production, processing and transportation of drugs. It is concluded that alternatives to the problem of rural youth involvement in the production of cannabis pass through the institutionalization of the reform, juvenile credit policy, education and vocational training for young people and for the legalization of cannabis growing.